Класифікація та тренди застосування технології 4.0. аграрними підприємствами - Чепіль, Г. В.; Панченко, А. В.; Chepil, G. V.; Panchenko, A. V. (Видавництво Львівської політехніки, 2024)
Стаття присвячена дослідженню теоретичних та практичних аспектів викорис- тання технологій 4.0 та цифрової трансформації у підприємствах агропромислового сектору. Проаналізовано основні тенденції розвитку цифрового сільського господарства в Україні та світі. Виділено й описано основні елементи концепції “розумного сільського господарства”. Наведено приклад розрахунку економічного ефекту від впровадження технологій точного хліборобства, який може бути значним для фермерських госпо- дарств.

The article is devoted to the study of theoretical and practical aspects of using Industry 4.0 technologies and digital transformation in the agricultural sector enterprises. The main trends in the development of digital agriculture in Ukraine and worldwide are analyzed. The authors identify and describe the main elements of the “smart agriculture” concept: • Unmanned aerial vehicles • Internet of Things • Wireless sensor networks • Data processing analytics tools • Artificial Intelligence • Software and applications. The article investigates that unmanned aerial vehicles are effective for monitoring the condition of plants and soils, making 3D maps, applying fertilizers and irrigating fields. Analytical data processing tools are presented, global trends in their use for summarizing historical data and forecasting weather conditions, yield and visualization of complex analytics are determined. The trends and ways of using robots with artificial intelligence by world farmers are presented, in particular for the design of unmanned tractors, automated sprayers, and shepherd robots. The ways of using wireless sensor networks by the world’s agrarians have been identified – the installation of physical and mechanical sensors for the analysis of natural phenomena, soil, and water. Cloud computing has been proven to be an important technology for global agribusiness, using it as a computing platform PAAS, software SAAS, infrastructure as a service IAAS. The article also systematizes programs and applications used by agrarians, in particular for managing agribusiness, optimizing the use of land, water, and fertilizers. The article examines the direct economic effects of the use of 4.0 technologies in agriculture. The effect of cost optimization and the effect of increased productivity when domestic farmers use 4.0 technologies are determined. An example of calculating the economic effect of implementing precision farming technologies, which can be significant for farming enterprises, is provided.
Classification and trends of industry 4.0 technology application by agricultural enterprises
Keywords: розумне сільське господарство; діджиталізація; цифрова трансформація; технології 4.0; ефективність виробництва; smart agriculture; digitization; digital transformation; Industry 4.0 technologies; production efficiency; 330.341